2018
DOI: 10.3389/fnagi.2018.00319
|View full text |Cite
|
Sign up to set email alerts
|

Smaller Hippocampal Volume and Degraded Peripheral Hearing Among Japanese Community Dwellers

Abstract: A growing body of literature has demonstrated that dementia and hearing loss are interrelated. Recent interest in dementia research has expanded to brain imaging analyses with auditory function. The aim of this study was to investigate the link between hearing ability, which was assessed using pure-tone audiometry, and the volume of brain regions, specifically the hippocampus, entorhinal cortex, Heschl’s gyrus, and total gray matter, using Freesurfer software and T1-weighted brain magnetic resonance imaging. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 44 publications
(52 reference statements)
2
34
0
1
Order By: Relevance
“…net) [20] was used for the cortical surface reconstructions and regional grey matter volume estimations. The technical details of these procedures have been described previously [7]. In short, the fully automated procedure in FreeSurfer involved preprocessing the subject's image data, segmenting the cortical grey matter and white matter (GM/WM), tessellating the GM/WM junction, inflating the folded surface tessellation patterns, and automatically correcting the topologic defects.…”
Section: Mri Data Acquisition and Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…net) [20] was used for the cortical surface reconstructions and regional grey matter volume estimations. The technical details of these procedures have been described previously [7]. In short, the fully automated procedure in FreeSurfer involved preprocessing the subject's image data, segmenting the cortical grey matter and white matter (GM/WM), tessellating the GM/WM junction, inflating the folded surface tessellation patterns, and automatically correcting the topologic defects.…”
Section: Mri Data Acquisition and Processingmentioning
confidence: 99%
“…We previously hypothesised that multiple nutritional deficiencies caused by an unbalanced diet might be a risk factor for cognitive decline and found that higher dietary diversity was associated with better cognitive function among older Japanese subjects [6]. However, we defined cognitive decline using the Mini-Mental State Examination [7]. A more objective measurement without the retest effect is needed to assess brain function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the right hippocampus of these individuals with moderate to severe hearing loss "looks" approximately 8 years older given that the normal shrinkage is approximately 0.5% annually for people above 60 years of age (Fjell et al, 2009). Previous cross-sectional research has found similar associations between pure-tone hearing loss and hippocampal volume in healthy older adults (Uchida et al, 2018). There have been similar findings in longitudinal studies showing accelerated decline in the hippocampus (Xu et al, 2019) and in the right parahippocampus across time in healthy older adults with pure-tone hearing loss.…”
Section: 1mentioning
confidence: 88%
“…Also cross-sectional work has shown that pure-tone hearing loss is related to neuroanatomical alterations of gray matter volume and thickness (Alfandari et al, 2018;Eckert et al, 2012;Rigters et al, 2018Rigters et al, , 2017Tuwaig et al, 2017;Rudner et al, 2019;Uchida et al, 2018;Ren et al, 2018;Armstrong et al, 2019;Neuschwander et al, 2019;Giroud et al, in prep., but see Profant et al, 2014).…”
Section: Frontal Cortical Thickness As a Correlate For Successful Sinmentioning
confidence: 99%